Effect of flaxseed oil on biochemical parameters, hormonal indexes and stereological changes in ovariectomized rats. Issue 2 (25th October 2020) - Tanideh, Romina; Delavari, Shirin; Farshad, Omid; Irajie, Cambyz; Javad Yavari Barhaghtalab, Mohammad; Koohpeyma, Farhad; Koohi‐Hosseinabadi, Omid; Jamshidzadeh, Akram; Tanideh, Nader; Iraji, Aida
Abstract: The ovariectomized rat is a widely used preclinical model for studying postmenopausal and its complications. In this study, the therapeutic effect of flaxseed oil on the ovariectomized adult rats was investigated. Our results showed that biochemical parameters including calcium, oestrogen and progesterone levels increase 8 weeks after ovariectomy in rats. Also, the amount of alkaline phosphatase decreased significantly after 8 weeks compared with the OVX rat. The healing potential of flaxseed oil was proven by successfully recovering the affected tissue and preventing the unpleasant symptoms of ovariectomized rats. The biological effects of flaxseed oil may be due to high amounts of fatty acids, phytoestrogens and an array of antioxidants. The results suggest that flaxseed oil can mimic the action of oestrogen and can be a potential treatment for hormone replacement therapy (HRT). Abstract : The potential use of flaxseed oil as the natural source for hormone replacement therapy on the ovariectomized rat model was investigated. The antioxidant properties and biochemical parameters including alkaline phosphatase, calcium, estrogen, and progesterone levels were determined in ovariectomy rats.